Synthesis and Characterization of Vinyltrimethoxysilane-Grafted Non-Swelling Clay. (2015) - Fernández, Laura G.; Cravero, Fernanda; Sánchez, María P.; Vivanco, Carlos De la Cruz; Gatti, Marcela
Abstract: The structural characteristics as well as the binding capacity of the functionalized halloysite/kaolinite from north Patagonia, Argentina were investigated. The sample was modified by immobilization of ligands containing vinyl (C=C) groups by covalent grafting with surface silanol groups. Silane grafted non swelling clays were synthesized by using vinyltrimethoxysilane (VTMS) via two different grafting reaction systems: (a) ethanol-water mixture and (b) xylene mixture. The resulting products were investigated using Infrared Spectroscopy (IR), X-ray diffraction (XRD), Thermogravimetric analysis (TGA-DTA), Microanalysis by dispersive energy (EDX) and Contact Angle for water (φ). The results indicate that the vinyl groups grafted at the mineral edges changed the hydrophilic nature of the clay mineral into hydrophobic. X-ray diffraction showed that their original structure had been preserved.